FUTBOLCHILARDA MAXSUS PSIXOLOGIK TAYYORGARLIK HOLATINI TADQIQ ETISHNING PSIXODIAGNOSTIK VOSITALARI - Jumabayev, T.J. (SCIENCE and SOCIETY, 2024)
In this article, psychological problems in football sports activities, mental functions of the individual, the general purpose of psychological training, concepts of voluntary actions, the high level of manifestation of sports motives in teenagers as well as others, the dynamic features of the formation of voluntary qualities are considered and opinions of scientists are analyzed in the preparation of athletes for the competition.